Function and strategies of making speech act of invitation in multicultural setting.: Function and strategies of making speech act of invitation in multicultural setting. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2021)
Abstract: The article gives a sight into the function of invitation namely, why people make the speech act of invitation and its categories. To make an acceptable invitation in international setting there are sequences that should be followed which are explained with examples. The examples give clear instructions for the language user about the sentence structures and common phrases that can be employed while making the speech act of invitation. Responding to invitation is another stage which should be acquired to provide suitable response to the inviter.